2018
DOI: 10.1007/s10484-018-9397-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bias of Interpretation in Type D Personality: Associations with Physiological Indices of Arousal

Abstract: It is argued that the Type D person experiences increased distress when encountering social situations, which results in altered stress responding. However, little is known about how Type D individuals behave or feel during social interactions. Using a within-subjects design, the present study examined the physiological arousal of Type D and non-Type D individuals when rating how they would deal with a number of hypothetical social situations. Results showed that across all social situations, Type D individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…Additionally, prior research has demonstrated that Type D may be more accurately represented as a continuous construct (Ferguson et al., 2009). Thus, in line with prior Type D studies, a continuous Type D construct was computed as the product of the SI and NA subscales (Howard & Hughes, 2013; Howard et al., 2011, 2018). All analyses were initially conducted using the traditional Type D dichotomy and were subsequently replicated using the continuous Type D interaction term (NA × SI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, prior research has demonstrated that Type D may be more accurately represented as a continuous construct (Ferguson et al., 2009). Thus, in line with prior Type D studies, a continuous Type D construct was computed as the product of the SI and NA subscales (Howard & Hughes, 2013; Howard et al., 2011, 2018). All analyses were initially conducted using the traditional Type D dichotomy and were subsequently replicated using the continuous Type D interaction term (NA × SI).…”
Section: Methodsmentioning
confidence: 99%
“…Given that Type D individuals are posited to feel tense, socially inhibited, and insecure when in the presence of other people (Denollet, 2005), this perception of lower social support is likely to be due to a cognitive bias of interpersonal interpretation among Type D individuals. Furthermore, this cognitive bias has been found to promote increased perceptions of negativity (perceived threat, anticipated distress, and difficulty forming verbal responses) during hypothetical social interactions among Type D individuals (Grynberg, Gidron, Denollet, & Luminet, 2012; Howard, O'Riordan, & Nolan, 2018). Additionally, prior studies have found this cognitive bias of interpersonal interpretation to influence patterns of physiological arousal among Type D individuals (Howard et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] TDP individuals may be subject to a biased interpretation of their health status dues to dysfunctional cognitive schemas that underlay the negative affective experiences through the erroneous interpretation of objective reality, leading to a more amplified negative affectivity and autonomic over activity. 48 In a clinical study, the presence of TDP was independently associated with the occurrence of ventricular arrhythmias as a marker of sympathetic dysregulation. 49 In both healthy individuals and CAD patients, the presence of TDP has been associated with increased diurnal cortisol release.…”
Section: Biological Substratementioning
confidence: 97%
“…To evaluate two dimensions of Type D personality individually, NA and SI can be regarded as continuous variables with the raw scores (Stevenson & Williams, 2014). The interaction term (NA 9 SI) was computed as the continuous Type D personality score (Howard et al, 2011;Howard, O'Riordan, & Nolan, 2018).…”
Section: Measurementsmentioning
confidence: 99%